Evaluation of Extended-Interval Dabigatran Dosing in Older Patients With Non-Valvular Atrial Fibrillation. (July 2021) - Ni, Lianfang; Chen, Xiahuan; Liu, Meilin; Fan, Yan; Fu, Zhifang; Sun, Dan; Zhao, Zhijie
Objective: To evaluate the safety and efficacy of extended-interval dabigatran dosing in older Chinese patients with non-valvular atrial fibrillation. Methods: We conducted an observational study on non-valvular atrial fibrillation patients administered dabigatran at different dosing intervals at the Department of Geriatrics, Peking University First Hospital, China. We enrolled 121 consecutive non-valvular atrial fibrillation patients aged ≥60 years on dabigatran therapy (mean age, 79.6 ± 7.4 years); they were administered conventional low-dose dabigatran (110 mg twice daily) or extended-interval dosing with dabigatran (110 mg every 16 h or every 24 h). All patients received follow-up care, and we evaluated the presence of bleeding and thromboembolic events. Results: All patients exhibited creatinine clearance greater than 30 mL/min with an average of 56.6 ± 17.3 mL/min. Sixty-two patients received extended-interval dosing with dabigatran at a mean dose of 117.1 ± 18.6 mg daily. Patients on extended-interval dosing were older; they exhibited lower creatinine clearance and bodyweight and higher CHA2 DS2 -VASc and HAS-BLED scores. The mean follow-up time was 25.8 ± 15.6 months. No significant differences were observed in the trough and peak values of the activated partial thromboplastin time and in thromboembolic or bleeding events between the 2 groups. Conclusion: Extended-interval dabigatran dosing in older patients with non-valvular atrial fibrillation and lower creatinine clearance can maintain activated partial thromboplastin time trough and peak values comparable to the conventional low dose. Physician-prescribed practices regarding dabigatran dosing intervals do not lead to worse outcomes in the above-mentioned population.